A hydrocracking catalyst based on molecular sieves and a method for its preparation
Patent Information
- Application Number
- CN202611213016.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-11
- Publication Date
- 2026-10-27
AI Technical Summary
[0007]鉴于此,本发明提出了一种基于分子筛的加氢裂化催化剂的制备方法,用以解决现有制备方法在刻蚀硅原子的同时,不可避免地会造成骨架铝原子的流失,导致分子筛结晶度下降、强Brnsted酸性位大量减少的问题
1.本发明先通过四丙基氢氧化铵对USY分子筛进行碱处理,利用四丙基氢氧化铵的动力学直径大于USY分子筛孔径的特性使得其仅在USY分子筛晶体表面和晶间缺陷处进行选择性刻蚀脱硅,引入介孔孔道的同时最大程度保留微孔骨架的完整性。再以偏铝酸钠为铝源对USY分子筛因脱硅产生的骨架硅羟基缺陷进行原位补铝,以修复骨架的拓扑结构,再经多次硝酸铵离子交换脱除骨架电荷平衡位的钠离子,然后结合水热晶化处理与焙烧处理修复骨架缺陷结构,在生成多级孔道结构的同时保持了分子筛高结晶度和高酸量。
Smart Images

Figure SMS_7 
Figure SMS_10
Abstract
Description
Technical Field
[0001] This invention relates to the field of hydrocracking catalysis technology, and more specifically, to a molecular sieve-based hydrocracking catalyst and its preparation method. Background Technology
[0002] Hydrocracking is primarily used for the refining of heavy oil, converting heavy feedstocks such as vacuum gas oil into gasoline, kerosene, and diesel. Hydrocracking catalysts are typical bifunctional catalysts, where molecular sieves provide the acidic centers required for cracking and isomerization, while supported metal sulfides provide the active hydrogenation centers. Y-type molecular sieves, due to their three-dimensional twelve-membered ring pore structure, high specific surface area, and tunable acidity, have become the most widely used acidic component in industrial hydrocracking catalysts.
[0003] However, conventional microporous Y molecular sieves have a pore size of about 0.74 nm, which presents significant mass transfer resistance for large molecular hydrocarbons in heavy feedstocks. This results in low utilization of acidic sites inside the molecular sieve, excessive residence time of reaction products in the pores, and easy occurrence of secondary cracking and condensation coking. Consequently, problems such as rapid decline in catalyst activity, low selectivity of middle distillate oil, and short service life are generated.
[0004] To address the aforementioned issues, existing technologies employ alkali treatment for desilication to introduce mesopores into molecular sieves, constructing a multi-level pore system. Alkali treatment can selectively remove silicon atoms from the molecular sieve framework, forming mesoporous channels within the crystal, effectively shortening molecular diffusion paths and improving the accessibility of acidic sites.
[0005] However, existing alkaline treatment technologies inevitably cause the loss of framework aluminum atoms while etching silicon atoms, leading to a decrease in the crystallinity of the molecular sieve and a weakening of its Br content. The number of nsted acid sites is greatly reduced; and the deeper the desilication, the larger the mesopore volume and the more severe the acid loss, which leads to a significant reduction in the catalyst's cracking activity.
[0006] Therefore, the present invention proposes a molecular sieve-based hydrocracking catalyst and its preparation method, which has important practical significance. Summary of the Invention
[0007] In view of this, the present invention proposes a method for preparing a hydrocracking catalyst based on molecular sieves, in order to solve the problem that existing preparation methods inevitably cause the loss of framework aluminum atoms while etching silicon atoms, leading to a decrease in the crystallinity of the molecular sieve and a weak Br content. The problem is that the number of nsted acid sites has been greatly reduced.
[0008] This invention proposes a method for preparing a molecular sieve-based hydrocracking catalyst, comprising the following steps: USY molecular sieve was added to a tetrapropylammonium hydroxide solution for alkaline treatment. After the treatment, the filter was filtered and washed to obtain a filter cake. The filter cake was dispersed in water, and sodium aluminate solution was added while stirring. After the process was completed, the pH of the system was adjusted to between 8.5 and 10.0 and stirring was continued to obtain the first mixed solution. After filtering and washing the first mixed solution, a first mixture is obtained. The first mixture is then added to an ammonium nitrate solution for dispersion, followed by an exchange reaction. After the reaction is completed, the mixture is filtered and washed. The dispersion, exchange reaction, and filtration and washing processes are repeated to obtain a second mixture. The second mixture was pulped and subjected to hydrothermal crystallization treatment. After the treatment, it was filtered, washed and dried, and then calcined to obtain modified multi-level porous Y molecular sieve. The modified hierarchical porous Y molecular sieve was mixed with pseudoboehmite, then mixed with dilute nitric acid, extruded into strips, dried, and calcined to obtain a catalyst support. Ammonium metatungstate and nickel nitrate hexahydrate are mixed to obtain an impregnation solution. The catalyst support is impregnated with the impregnation solution. After the impregnation is completed, the catalyst is obtained by post-treatment.
[0009] Furthermore, the alkali treatment specifically includes: USY molecular sieve was added to a 0.1 mol / L tetrapropylammonium hydroxide solution at a mass ratio of 1:10 and stirred at 75 °C for 1 h.
[0010] Furthermore, the concentration of the sodium aluminate solution is 24 g / L, and the mass of sodium aluminate in the added sodium aluminate solution is 3.2% of the mass of the USY molecular sieve.
[0011] Furthermore, the exchange reaction specifically includes: The first mixture was added to a 1 mol / L ammonium nitrate solution at a mass ratio of 1:10, and the mixture was stirred at 90°C for 1.5 h.
[0012] Furthermore, the hydrothermal crystallization treatment is performed at a temperature of 120°C for a duration of 6 hours.
[0013] Furthermore, the calcination process is carried out in an air atmosphere, at a calcination temperature of 550°C, and for a calcination time of 4 hours.
[0014] Furthermore, the mass ratio of the modified hierarchical porous Y molecular sieve to pseudoboehmite is (40~70):(30~60).
[0015] Furthermore, the ammonium metatungstate and nickel nitrate hexahydrate are in a mass ratio of 1.57:1; The impregnation process specifically involves spraying the impregnation solution onto the catalyst support at a solid-liquid ratio of 100:65 (g / ml).
[0016] Furthermore, the post-processing specifically includes: After impregnation, the mixture was left to stand at room temperature for 3 hours, dried at 110°C for 8 hours, and then calcined at 480°C in air for 4 hours.
[0017] The present invention also provides the aforementioned molecular sieve-based hydrocracking catalyst.
[0018] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. This invention first treats USY molecular sieves with tetrapropylammonium hydroxide using an alkaline method. Utilizing the characteristic that the kinetic diameter of tetrapropylammonium hydroxide is larger than the pore size of the USY molecular sieve, it selectively etches and removes silicon only at the surface and intergranular defects of the USY molecular sieve crystals, introducing mesoporous channels while preserving the integrity of the microporous framework to the greatest extent. Then, sodium aluminate is used as the aluminum source to in-situ replenish aluminum to the silanol defects in the framework caused by desilication of the USY molecular sieve, repairing the framework topology. Next, multiple ammonium nitrate ion exchanges remove sodium ions from the charge balance sites of the framework. Finally, hydrothermal crystallization and calcination are combined to repair the framework defect structure, generating a multi-level pore structure while maintaining the high crystallinity and high acidity of the molecular sieve. Detailed Implementation
[0019] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention. It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the present invention.
[0020] Furthermore, regarding the numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.
[0021] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.
[0022] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be apparent to those skilled in the art. This specification and embodiments are merely exemplary.
[0023] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.
[0024] This invention provides a method for preparing a molecular sieve-based hydrocracking catalyst, comprising the following steps: USY molecular sieve was added to a tetrapropylammonium hydroxide solution for alkaline treatment. After the treatment, the filter was filtered and washed to obtain a filter cake. The filter cake was dispersed in water, and sodium aluminate solution was added while stirring. After the process was completed, the pH of the system was adjusted to between 8.5 and 10.0 and stirring was continued to obtain the first mixed solution. After filtering and washing the first mixed solution, a first mixture is obtained. The first mixture is then added to an ammonium nitrate solution for dispersion, followed by an exchange reaction. After the reaction is completed, the mixture is filtered and washed. The dispersion, exchange reaction, and filtration and washing processes are repeated to obtain a second mixture. The second mixture was pulped and subjected to hydrothermal crystallization treatment. After the treatment, it was filtered, washed and dried, and then calcined to obtain modified multi-level porous Y molecular sieve. The modified hierarchical porous Y molecular sieve was mixed with pseudoboehmite, then mixed with dilute nitric acid, extruded into strips, dried, and calcined to obtain a catalyst support. Ammonium metatungstate and nickel nitrate hexahydrate are mixed to obtain an impregnation solution. The catalyst support is impregnated with the impregnation solution. After the impregnation is completed, the catalyst is obtained by post-treatment.
[0025] Specifically, the water is preferably deionized water.
[0026] Specifically, after filtration and washing, when the filter cake is obtained, the filter is filtered and washed with deionized water until the pH of the filtrate is 7.5.
[0027] Specifically, when the filter cake is added to water and dispersed, the mass ratio of the filter cake to the water is 1:7.
[0028] Specifically, after adjusting the pH of the system to between 8.5 and 10.0, and continuing to stir: adjust the pH of the system to between 8.5 and 10.0 with 8% dilute nitric acid, and then stir the reaction at 50°C for 2 hours.
[0029] Specifically, the dispersion, exchange reaction and filtration washing were repeated twice.
[0030] Specifically, when pulping the first mixture, the first mixture is added to deionized water at a mass ratio of 1:4 and pulped into a slurry.
[0031] Specifically, after filtration, washing, and drying, and followed by calcination to obtain the modified multi-level porous Y molecular sieve, the drying temperature was 110℃ and the drying time was 8h.
[0032] Understandably, this invention first treats the USY molecular sieve with tetrapropylammonium hydroxide using an alkaline method. Utilizing the characteristic that the kinetic diameter of tetrapropylammonium hydroxide is larger than the pore size of the USY molecular sieve, it selectively etches and desilicates only at the surface and intergranular defects of the USY molecular sieve crystals, introducing mesoporous channels while preserving the integrity of the microporous framework to the greatest extent possible. Then, sodium aluminate is used as the aluminum source to in-situ replenish the silanol defects in the framework caused by desilication of the USY molecular sieve, repairing the framework's topology. Next, multiple ammonium nitrate ion exchanges remove sodium ions from the framework's charge balance sites. Finally, a combination of hydrothermal crystallization and calcination treatments repairs the framework's defective structure, generating a multi-level pore structure while maintaining the molecular sieve's high crystallinity and high acidity.
[0033] In this invention, the alkali treatment specifically includes: USY molecular sieve was added to a 0.1 mol / L tetrapropylammonium hydroxide solution at a mass ratio of 1:10 and stirred at 75 °C for 1 h.
[0034] Specifically, USY molecular sieves were added to a 0.1 mol / L tetrapropylammonium hydroxide solution at a mass ratio of 1:10, stirred at 75°C for 1 hour, filtered, and washed with deionized water until the pH of the filtrate was 7.5 to obtain a filter cake.
[0035] It is understandable that the kinetic diameter of tetrapropylammonium hydroxide molecules is about 0.9 nm, which is larger than the micropore diameter of Y molecular sieve (0.74 nm). Therefore, it cannot enter the interior of the molecular sieve micropores and can only selectively etch and desiliconize at the outer surface of the crystal and intergranular defects. This allows it to introduce mesoporous channels into the molecular sieve crystal while preserving the integrity of the microporous framework to the greatest extent and avoiding a significant decrease in crystallinity.
[0036] In this invention, the concentration of the sodium aluminate solution is 24 g / L, and the mass of sodium aluminate in the added sodium aluminate solution is 3.2% of the mass of the USY molecular sieve.
[0037] Specifically, the filter cake is dispersed in deionized water at a mass ratio of 1:7, and a sodium aluminate solution with a concentration of 24 g / L is added dropwise while stirring. The addition is stopped when the mass of sodium aluminate in the added sodium aluminate solution is 3.2% of the mass of the USY molecular sieve. After the addition is complete, the pH of the system is adjusted to between 8.5 and 10.0 with 8% dilute nitric acid. Then, the reaction is continued to be stirred at 50°C for 2.0 h to obtain the first mixed solution.
[0038] It is understandable that after alkali treatment, USY molecular sieve generates a large number of silanol defect sites and lattice vacancies on the molecular sieve framework. In a weakly alkaline hydrothermal environment, aluminate ions migrate to the framework defects through diffusion, and undergo condensation reaction with the silanols at the defect sites, anchoring aluminum atoms to the framework vacancies and initially repairing the framework topology.
[0039] In this invention, the exchange reaction specifically refers to: The first mixture was added to a 1 mol / L ammonium nitrate solution at a mass ratio of 1:10, and the mixture was stirred at 90°C for 1.5 h.
[0040] Specifically, the first mixed solution is filtered and washed with deionized water until the filtrate is free of sodium ions to obtain the first mixture. The first mixture is added to a 1 mol / L ammonium nitrate solution at a mass ratio of 1:10 and stirred at 90°C for 1.5 h. After completion, the mixture is filtered and washed. The dispersion, exchange reaction and filtration and washing are repeated twice to obtain the second mixture.
[0041] Understandably, after treatment with sodium aluminate solution, sodium ions, as charge-balancing cations, occupy ion exchange sites. The molecular sieve is in the sodium form and lacks proton acidity. Subsequently, utilizing the ion exchange between ammonium and sodium ions, ammonium ions from ammonium nitrate solution replace the sodium ions occupying the charge-balancing sites in the framework. Through multiple replacements, sodium ions bound to the framework are removed, paving the way for subsequent calcination to form Br. The nsted acid site provides the prerequisite.
[0042] In this invention, the hydrothermal crystallization treatment is performed at a temperature of 120°C for 6 hours.
[0043] The roasting process was carried out in an air atmosphere, at a roasting temperature of 550°C, and for 4 hours.
[0044] Specifically, the second mixture is added to deionized water at a mass ratio of 1:4 to form a slurry. The slurry is then transferred to a stainless steel reactor lined with polytetrafluoroethylene and subjected to hydrothermal crystallization at 120°C for 6 hours. After crystallization, the mixture is cooled to room temperature, filtered, and washed until the filtrate is neutral. The filtrate is then dried at 110°C for 8 hours and calcined at 550°C in air for 4 hours to obtain the modified hierarchical porous Y molecular sieve.
[0045] Understandably, hydrothermal conditions promote the rearrangement and migration of framework atoms, enabling the replacement aluminum atoms to form chemical bonds with surrounding silicon atoms, repairing framework defects caused by desilication, and improving the crystallinity and hydrothermal stability of the molecular sieve. During calcination, the ammonium-type molecular sieve decomposes, releasing ammonia gas and forming bridged hydroxyl structures, i.e., Br... The nsted acidic centers give the molecular sieve the proton acidity required for the cracking reaction.
[0046] In this invention, the mass ratio of the modified hierarchical porous Y molecular sieve to pseudoboehmite is (40~70):(30~60).
[0047] Specifically, modified hierarchical porous Y molecular sieve and pseudoboehmite were mixed according to a mass ratio of (40~70):(30~60), and then 4% dilute nitric acid (65% of the total mass of the modified hierarchical porous Y molecular sieve and pseudoboehmite) was added. The mixture was kneaded for 20 minutes to form a paste, which was then extruded into strips with a diameter of 1.8 mm. The paste was dried at 110 °C for 8 hours and then calcined at 550 °C for 4 hours in air to obtain the catalyst support.
[0048] In this invention, the ammonium metatungstate and nickel nitrate hexahydrate are in a mass ratio of 1.57:1; The impregnation process specifically involves spraying the impregnation solution onto the catalyst support at a solid-liquid ratio of 100:65 (g / ml).
[0049] The post-processing specifically includes: After impregnation, the mixture was left to stand at room temperature for 3 hours, dried at 110°C for 8 hours, and then calcined at 480°C in air for 4 hours.
[0050] Specifically, the mass ratio of ammonium metatungstate, nickel nitrate hexahydrate, and deionized water is 1.57:1:3.17.
[0051] Specifically, ammonium metatungstate and nickel nitrate hexahydrate were mixed and dissolved in deionized water at a mass ratio of ammonium metatungstate: nickel nitrate hexahydrate: deionized water = 1.57:1:3.17 to obtain an impregnation solution. The impregnation solution was sprayed evenly onto the catalyst support at a solid-liquid ratio of 100:65 (g / ml). After spraying, the solution was allowed to stand at room temperature for 3 hours, dried at 110°C for 8 hours, and then calcined at 480°C in air for 4 hours.
[0052] Example 1 S1. Add USY molecular sieve to a 0.1 mol / L tetrapropylammonium hydroxide solution at a mass ratio of 1:10, stir at 75°C for 1 hour, filter, and wash with deionized water until the pH of the filtrate is 7.5 to obtain filter cake. S2. Disperse the filter cake in deionized water at a mass ratio of 1:7, and add a sodium aluminate solution with a concentration of 24 g / L dropwise while stirring. Stop adding the sodium aluminate solution when the mass of sodium aluminate in the added sodium aluminate solution is 3.2% of the mass of the USY molecular sieve. After the addition is completed, adjust the pH of the system to between 8.5 and 10.0 with dilute nitric acid with a mass concentration of 8%, and then continue to stir the reaction at 50°C for 2.0 h to obtain the first mixed solution. S3. After filtering the first mixed solution, wash it with deionized water until the filtrate is free of sodium ions to obtain the first mixture. Add the first mixture to a 1 mol / L ammonium nitrate solution at a mass ratio of 1:10, stir and react at 90°C for 1.5 h. After completion, filter and wash, repeat the dispersion, exchange reaction and filtration and washing twice to obtain the second mixture. S4. The second mixture is added to deionized water at a mass ratio of 1:4 and slurryed to form a slurry. The slurry is transferred into a stainless steel reactor with a polytetrafluoroethylene liner and subjected to hydrothermal crystallization treatment at 120°C for 6 hours. After crystallization, the mixture is cooled to room temperature, filtered, and washed until the filtrate is neutral. The filtrate is dried at 110°C for 8 hours and then calcined at 550°C in air atmosphere for 4 hours to obtain the modified multi-level porous Y molecular sieve. S5. The modified hierarchical porous Y molecular sieve and pseudoboehmite were mixed at a mass ratio of 70:30. Then, 65% of the total mass of the modified hierarchical porous Y molecular sieve and pseudoboehmite was added to a 4% dilute nitric acid solution. The mixture was kneaded for 20 minutes until a paste was formed. The paste was then extruded into strips with a diameter of 1.8 mm and dried at 110 °C for 8 hours. Finally, it was calcined at 550 °C in air for 4 hours to obtain the catalyst support. S6. Ammonium metatungstate and nickel nitrate hexahydrate were added to deionized water and mixed and dissolved according to the mass ratio of ammonium metatungstate: nickel nitrate hexahydrate: deionized water = 1.57:1:3.17 to obtain an impregnation solution. The impregnation solution was sprayed evenly onto the catalyst support at a solid-liquid ratio of 100:65 (g / ml). After spraying, the solution was allowed to stand at room temperature for 3 hours, dried at 110℃ for 8 hours, and then calcined at 480℃ for 4 hours in air atmosphere to obtain a hydrocracking catalyst based on molecular sieve.
[0053] Example 2 S1. Add USY molecular sieve to a 0.1 mol / L tetrapropylammonium hydroxide solution at a mass ratio of 1:10, stir at 75°C for 1 hour, filter, and wash with deionized water until the pH of the filtrate is 7.5 to obtain filter cake. S2. Disperse the filter cake in deionized water at a mass ratio of 1:7, and add a sodium aluminate solution with a concentration of 24 g / L dropwise while stirring. Stop adding the sodium aluminate solution when the mass of sodium aluminate in the added sodium aluminate solution is 3.2% of the mass of the USY molecular sieve. After the addition is completed, adjust the pH of the system to between 8.5 and 10.0 with dilute nitric acid with a mass concentration of 8%, and then continue to stir the reaction at 50°C for 2.0 h to obtain the first mixed solution. S3. After filtering the first mixed solution, wash it with deionized water until the filtrate is free of sodium ions to obtain the first mixture. Add the first mixture to a 1 mol / L ammonium nitrate solution at a mass ratio of 1:10, stir and react at 90°C for 1.5 h. After completion, filter and wash, repeat the dispersion, exchange reaction and filtration and washing twice to obtain the second mixture. S4. The second mixture is added to deionized water at a mass ratio of 1:4 and slurryed to form a slurry. The slurry is transferred into a stainless steel reactor with a polytetrafluoroethylene liner and subjected to hydrothermal crystallization treatment at 120°C for 6 hours. After crystallization, the mixture is cooled to room temperature, filtered, and washed until the filtrate is neutral. The filtrate is dried at 110°C for 8 hours and then calcined at 550°C in air atmosphere for 4 hours to obtain the modified multi-level porous Y molecular sieve. S5. The modified hierarchical porous Y molecular sieve and pseudoboehmite were mixed at a mass ratio of 55:45. Then, 65% of the total mass of the modified hierarchical porous Y molecular sieve and pseudoboehmite was added to a 4% dilute nitric acid solution. The mixture was kneaded for 20 minutes until a paste was formed. The paste was then extruded into strips with a diameter of 1.8 mm and dried at 110 °C for 8 hours. Finally, it was calcined at 550 °C in air for 4 hours to obtain the catalyst support. S6. Ammonium metatungstate and nickel nitrate hexahydrate were added to deionized water and mixed and dissolved according to the mass ratio of ammonium metatungstate: nickel nitrate hexahydrate: deionized water = 1.57:1:3.17 to obtain an impregnation solution. The impregnation solution was sprayed evenly onto the catalyst support at a solid-liquid ratio of 100:65 (g / ml). After spraying, the solution was allowed to stand at room temperature for 3 hours, dried at 110℃ for 8 hours, and then calcined at 480℃ for 4 hours in air atmosphere to obtain a hydrocracking catalyst based on molecular sieve.
[0054] Example 3 S1. Add USY molecular sieve to a 0.1 mol / L tetrapropylammonium hydroxide solution at a mass ratio of 1:10, stir at 75°C for 1 hour, filter, and wash with deionized water until the pH of the filtrate is 7.5 to obtain filter cake. S2. Disperse the filter cake in deionized water at a mass ratio of 1:7, and add a sodium aluminate solution with a concentration of 24 g / L dropwise while stirring. Stop adding the sodium aluminate solution when the mass of sodium aluminate in the added sodium aluminate solution is 3.2% of the mass of the USY molecular sieve. After the addition is completed, adjust the pH of the system to between 8.5 and 10.0 with dilute nitric acid with a mass concentration of 8%, and then continue to stir the reaction at 50°C for 2.0 h to obtain the first mixed solution. S3. After filtering the first mixed solution, wash it with deionized water until the filtrate is free of sodium ions to obtain the first mixture. Add the first mixture to a 1 mol / L ammonium nitrate solution at a mass ratio of 1:10, stir and react at 90°C for 1.5 h. After completion, filter and wash, repeat the dispersion, exchange reaction and filtration and washing twice to obtain the second mixture. S4. The second mixture is added to deionized water at a mass ratio of 1:4 and slurryed to form a slurry. The slurry is transferred into a stainless steel reactor with a polytetrafluoroethylene liner and subjected to hydrothermal crystallization treatment at 120°C for 6 hours. After crystallization, the mixture is cooled to room temperature, filtered, and washed until the filtrate is neutral. The filtrate is dried at 110°C for 8 hours and then calcined at 550°C in air atmosphere for 4 hours to obtain the modified multi-level porous Y molecular sieve. S5. The modified hierarchical porous Y molecular sieve and pseudoboehmite were mixed at a mass ratio of 40:60. Then, 65% of the total mass of the modified hierarchical porous Y molecular sieve and pseudoboehmite was added to a 4% dilute nitric acid solution. The mixture was kneaded for 20 minutes until a paste was formed. The paste was then extruded into strips with a diameter of 1.8 mm and dried at 110 °C for 8 hours. Finally, it was calcined at 550 °C in air for 4 hours to obtain the catalyst support. S6. Ammonium metatungstate and nickel nitrate hexahydrate were added to deionized water and mixed and dissolved according to the mass ratio of ammonium metatungstate: nickel nitrate hexahydrate: deionized water = 1.57:1:3.17 to obtain an impregnation solution. The impregnation solution was sprayed evenly onto the catalyst support at a solid-liquid ratio of 100:65 (g / ml). After spraying, the solution was allowed to stand at room temperature for 3 hours, dried at 110℃ for 8 hours, and then calcined at 480℃ for 4 hours in air atmosphere to obtain a hydrocracking catalyst based on molecular sieve.
[0055] Comparative Example 1 S1. USY molecular sieve was added to a 0.2 mol / L NaOH solution at a mass ratio of 1:10 and stirred at 75°C for 1 hour. After stirring, the mixture was filtered and washed with deionized water until the pH of the filtrate was 7.5, thus obtaining a conventional multi-level porous molecular sieve. S5. After mixing conventional multi-level porous molecular sieve and pseudoboehmite in a mass ratio of 55:45, add 4% dilute nitric acid, which accounts for 65% of the total mass of conventional multi-level porous molecular sieve and pseudoboehmite. Knead for 20 minutes to form a paste, extrude it into strips with a diameter of 1.8 mm, dry it at 110°C for 8 hours, and then calcine it at 550°C in air for 4 hours to obtain the catalyst support. S6. Ammonium metatungstate and nickel nitrate hexahydrate were added to deionized water and mixed and dissolved according to the mass ratio of ammonium metatungstate: nickel nitrate hexahydrate: deionized water = 1.57:1:3.17 to obtain an impregnation solution. The impregnation solution was sprayed evenly onto the catalyst support at a solid-liquid ratio of 100:65 (g / ml). After spraying, the solution was allowed to stand at room temperature for 3 hours, dried at 110℃ for 8 hours, and then calcined at 480℃ for 4 hours in air atmosphere to obtain a hydrocracking catalyst based on molecular sieve.
[0056] Comparative Example 2 S1. Add USY molecular sieve to a 0.1 mol / L tetrapropylammonium hydroxide solution at a mass ratio of 1:10, stir at 75°C for 1 hour, filter, and wash with deionized water until the pH of the filtrate is 7.5 to obtain filter cake. S2. Disperse the filter cake in deionized water at a mass ratio of 1:7, and add a sodium aluminate solution with a concentration of 24 g / L dropwise while stirring. Stop adding the sodium aluminate solution when the mass of sodium aluminate in the added sodium aluminate solution is 3.2% of the mass of the USY molecular sieve. After the addition is completed, adjust the pH of the system to between 8.5 and 10.0 with dilute nitric acid with a mass concentration of 8%, and then continue to stir the reaction at 50°C for 2.0 h to obtain the first mixed solution. S3. After filtering the first mixed solution, a second mixture is obtained. The second mixture is added to deionized water at a mass ratio of 1:4 and slurryed to form a slurry. The slurry is transferred into a stainless steel reactor with a polytetrafluoroethylene liner and subjected to hydrothermal crystallization treatment at 120°C for 6 hours. After crystallization, the mixture is cooled to room temperature, filtered, and washed until the filtrate is neutral. The filtrate is dried at 110°C for 8 hours and then calcined at 550°C in air atmosphere for 4 hours to obtain the modified hierarchical porous Y molecular sieve. S4. The modified hierarchical porous Y molecular sieve and pseudoboehmite were mixed at a mass ratio of 55:45. Then, 65% of the total mass of the modified hierarchical porous Y molecular sieve and pseudoboehmite was added to a 4% dilute nitric acid solution. The mixture was kneaded for 20 minutes until a paste was formed. The paste was then extruded into strips with a diameter of 1.8 mm and dried at 110 °C for 8 hours. Finally, it was calcined at 550 °C in air for 4 hours to obtain the catalyst support. S5. Ammonium metatungstate and nickel nitrate hexahydrate were mixed and dissolved in deionized water at a mass ratio of 1.57:1:3.17 to obtain an impregnation solution. The impregnation solution was sprayed evenly onto the catalyst support at a solid-liquid ratio of 100:65 (g / ml). After spraying, the solution was allowed to stand at room temperature for 3 hours, dried at 110℃ for 8 hours, and then calcined at 480℃ for 4 hours in air atmosphere to obtain a hydrocracking catalyst based on molecular sieve.
[0057] Effect test 1. Molecular sieve characterization and detection: Test samples: Molecular sieves prepared in Example 2, Comparative Example 1, and Comparative Example 2 Detection method: The relative crystallinity of the samples was determined using an X-ray diffractometer, with the raw material USY molecular sieve as a reference sample (crystallization was defined as 100%), and the relative crystallinity of the samples was calculated by the sum of the peak areas of the characteristic diffraction peaks.
[0058] The elemental composition of the sample was determined using X-ray fluorescence spectrometry, and the molar ratio of SiO2 to Al2O3 was calculated based on the mass fractions of silicon and aluminum.
[0059] The mass fraction of Na2O in the sample was determined by flame atomic absorption spectrometry. After the sample was digested with hydrofluoric acid and nitric acid, the sodium content was tested and converted into the mass fraction of Na2O.
[0060] The total pore volume and mesopore volume were determined by a fully automated specific surface area and pore size analyzer using a low-temperature nitrogen adsorption-desorption method. The total pore volume was calculated by converting the amount of nitrogen adsorbed at a relative pressure of 0.99. The mesopore volume was the difference between the total pore volume and the micropore volume.
[0061] The total acid content was determined by the NH3 temperature-programmed desorption method. The sample was pretreated at 500℃ for 1 h in a helium atmosphere, cooled to 100℃ to adsorb NH3 until saturation, and then the physically adsorbed NH3 was removed by purging. The temperature was then increased to 600℃ at a rate of 10℃ / min. The total acid content was quantitatively calculated by the desorption peak area.
[0062] Determination of strong Br by pyridine adsorption infrared spectroscopy (Py-IR) The nsted acid content was determined by pretreating the sample at 400℃ for 2 hours under vacuum after tableting, followed by cooling to 150℃ for 30 minutes to adsorb pyridine. After vacuum desorption of the physically adsorbed pyridine, the infrared spectrum of the desorbed pyridine was collected at 350℃. The 1540 cm⁻¹ value was then used as the reference. -1 Calculation of the peak area of the characteristic peak (Br) nsted acid amount.
[0063] The test results are shown in Table 1: Characterization and detection results of molecular sieve samples
[0064] Table 1 shows that compared with Comparative Example 1, which was treated with conventional NaOH alkali, the relative crystallinity of the molecular sieve in Example 2 increased by 17.2 percentage points, the proportion of mesoporous pore volume was higher, and the total acidity increased by 54.4%, with stronger Br content. The proportion of nsted acid increased by 14.1 percentage points.
[0065] Compared to Comparative Example 2, which did not undergo ammonium exchange, the Na₂O mass fraction in Example 2 decreased from 1.85% to 0.07%, the total acidity increased fourfold, and the strong Br₂ content increased significantly. The proportion of nsted acid increased by nearly 40 percentage points, which fully demonstrates that ammonium salt ion exchange can effectively remove sodium ions from the skeletal charge balance sites.
[0066] 2. Catalytic performance test Detection method: The catalysts prepared in Example 2, Comparative Example 1, and Comparative Example 2 were tested on a 200 mL fixed-bed hydrocracking experimental apparatus. The catalyst loading was 100 mL, and the evaluation feedstock was Daqing vacuum gas oil (VGO). The catalyst was first subjected to dimethyl disulfide sulfidation treatment, and the feedstock was switched after sulfidation. The reaction pressure was 14 MPa, the hydrogen-to-oil volume ratio was 1500:1, and the volume hourly space velocity was 1.0 h⁻¹. -1 The reaction temperature was 380℃. After 48 hours of stable operation, product samples were collected for analysis. The VGO conversion rate, middle distillate oil selectivity, middle distillate oil yield, gas yield, and activity reduction rate of the corresponding catalyst were calculated. Wherein, VGO conversion rate = (mass of feed fraction above 350℃ - mass of product fraction above 350℃) / mass of feed fraction above 350℃ × 100% Middle distillate oil selectivity = (Mass of the 165-350℃ fraction in the product / Mass of the converted fraction above 350℃) × 100% Middle distillate oil yield = VGO conversion × Middle distillate oil selectivity × 100% Gas yield = (Total mass of C1-C4 gaseous hydrocarbons in the product / Total mass of feed) × 100% Activity decline rate after 1000 hours = (Initial VGO conversion rate - VGO conversion rate after 1000 hours of continuous operation) / Initial VGO conversion rate × 100% The test results are shown in Table 2: Table 2 Catalytic performance test results
[0067] Note: Comparative Example 2 was not subjected to a 1000-hour stability test due to its low initial activity.
[0068] As shown in Table 2, compared with Comparative Example 1 treated with conventional alkali, the VGO conversion rate of the catalyst in Example 2 increased by 9.4 percentage points, the selectivity of middle distillate oil increased by 6.7 percentage points, and the yield of middle distillate oil increased by 12.1 percentage points, while the gas yield decreased by 1.9 percentage points. It can be seen that the mesoporous structure of the catalyst of the present invention reduces the diffusion resistance of large molecular hydrocarbons, improves the utilization rate of acid sites, and ensures the cracking activity with sufficient strong Brønsted acid sites. At the same time, the rapid diffusion and desorption of products reduces secondary cracking, thereby achieving a simultaneous improvement in activity and selectivity of middle distillate oil.
[0069] The VGO conversion rate of the catalyst in Comparative Example 2, which did not undergo ammonium exchange, was only 32.5%, which was much lower than that in Example 2. This is because the catalyst's cracking activity was greatly lost after sodium ions blocked the acidic sites.
[0070] In Example 2, the catalyst activity decreased by only 6.8% after 1000 hours of operation, which was 4.5 percentage points lower than that of Comparative Example 1.
[0071] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention can have various modifications and variations. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention. Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the specific implementation of the present invention. Any modifications or equivalent substitutions that do not depart from the spirit and scope of the present invention should be covered within the protection scope of the claims of the present invention.
Claims
1. A method for preparing a hydrocracking catalyst based on molecular sieves, characterized in that, Includes the following steps: USY molecular sieve was added to a tetrapropylammonium hydroxide solution for alkaline treatment. After the treatment, the filter was filtered and washed to obtain a filter cake. The filter cake was dispersed in water, and sodium aluminate solution was added while stirring. After the process was completed, the pH of the system was adjusted to between 8.5 and 10.0 and stirring was continued to obtain the first mixed solution. After filtering and washing the first mixed solution, a first mixture is obtained. The first mixture is then added to an ammonium nitrate solution for dispersion, followed by an exchange reaction. After the reaction is completed, the mixture is filtered and washed. The dispersion, exchange reaction, and filtration and washing processes are repeated to obtain a second mixture. The second mixture was pulped and subjected to hydrothermal crystallization treatment. After the treatment, it was filtered, washed and dried, and then calcined to obtain modified multi-level porous Y molecular sieve. The modified hierarchical porous Y molecular sieve was mixed with pseudoboehmite, then mixed with dilute nitric acid, extruded into strips, dried, and calcined to obtain a catalyst support. Ammonium metatungstate and nickel nitrate hexahydrate are mixed to obtain an impregnation solution. The catalyst support is impregnated with the impregnation solution. After the impregnation is completed, the catalyst is obtained by post-treatment.
2. The method for preparing the molecular sieve-based hydrocracking catalyst according to claim 1, characterized in that, The alkaline treatment specifically involves: USY molecular sieve was added to a 0.1 mol / L tetrapropylammonium hydroxide solution at a mass ratio of 1:10 and stirred at 75 °C for 1 h.
3. The method for preparing the molecular sieve-based hydrocracking catalyst according to claim 1, characterized in that, The concentration of the sodium aluminate solution is 24 g / L, and the mass of sodium aluminate in the added sodium aluminate solution is 3.2% of the mass of the USY molecular sieve.
4. The molecular sieve-based hydrocracking catalyst according to claim 1, characterized in that, The exchange reaction is specifically as follows: The first mixture was added to a 1 mol / L ammonium nitrate solution at a mass ratio of 1:10, and the mixture was stirred at 90°C for 1.5 h.
5. The method for preparing the molecular sieve-based hydrocracking catalyst according to claim 1, characterized in that, The hydrothermal crystallization treatment was performed at a temperature of 120°C for 6 hours.
6. The method for preparing the molecular sieve-based hydrocracking catalyst according to claim 1, characterized in that, The roasting process was carried out in an air atmosphere, at a roasting temperature of 550°C, and for 4 hours.
7. The method for preparing the molecular sieve-based hydrocracking catalyst according to claim 1, characterized in that, The mass ratio of the modified hierarchical porous Y molecular sieve to pseudoboehmite is (40~70):(30~60).
8. The method for preparing the molecular sieve-based hydrocracking catalyst according to claim 1, characterized in that, The ammonium metatungstate and nickel nitrate hexahydrate are mixed in a mass ratio of 1.57:1; The impregnation process specifically involves spraying the impregnation solution onto the catalyst support at a solid-liquid ratio of 100:65 (g / ml).
9. The method for preparing the molecular sieve-based hydrocracking catalyst according to claim 1, characterized in that, The post-processing specifically includes: After impregnation, the mixture was left to stand at room temperature for 3 hours, dried at 110°C for 8 hours, and then calcined at 480°C in air for 4 hours.
10. The molecular sieve-based hydrocracking catalyst prepared by the method for preparing the molecular sieve-based hydrocracking catalyst according to any one of claims 1 to 9.